A comprehensive systematic review of evidence on the effectiveness and appropriateness of undergraduate nursing curricula. - Jayasekara, Rasika; Schultz, Tim; McCutcheon, Helen (International Journal of Evidence-Based Healthcare, 2006)
Objectives The objective of this review was to appraise and synthesise the best available evidence on the effectiveness and appropriateness of undergraduate nursing curricula. Inclusion criteria This review considered research papers that addressed the effectiveness and appropriateness of undergraduate nursing curricula. Studies of higher evidence levels were given priority over lower-evidence studies. Participants of interest were undergraduate nursing students, nursing staff and healthcare consumers. Nursing staff outcomes, consumer outcomes and system outcomes (e.g. competency, satisfaction, critical thinking skills, healthcare consumer rights and cost-effectiveness) that impact on the evaluation of undergraduate nursing curricula were considered in the review. Search strategy The search strategy sought to find both published and unpublished studies and reports limited to the English language. An initial limited search of MEDLINE and CINAHL was undertaken, followed by an analysis of the text contained in the title and abstract, and of the index terms used to describe the article. A second extensive search was then undertaken using all identified key words and index terms. Finally, the reference list of all identified reports and articles was searched for additional studies. Methodological quality Each paper was assessed by two independent reviewers for methodological quality before inclusion in the review using an appropriate critical appraisal instrument from the Unified Management, Assessment and Review of Information (SUMARI) package. Results A total of 16 papers, experimental and textual in nature, were included in the review. The majority of papers was descriptive and examined the relationships between nursing curricula and specific learning outcomes such as critical thinking skills. Because of the diverse nature of these papers, meta-analysis of the results was not possible and this section of the review is presented in narrative form. In this review, four undergraduate nursing curriculum models were identified: integrated curriculum, subject-centred curriculum, problem-based learning, and an integrated critical thinking model. It was possible to examine the effectiveness of an integrated curriculum model and a subject-centred curriculum model; however, the other two models could not be compared because of a lack of evidence. Conclusion The evidence regarding the effectiveness and appropriateness of undergraduate nursing curricula is notably weak because of the paucity of high-quality comparative studies and meaningful outcome measures of available studies. Therefore, no strong conclusion can be made regarding the effectiveness and appropriateness of undergraduate nursing curricula